(untitled) (CIPEEX, 2025)
Introduction: Opioid use disorder (OUD) is a complex disease and public health threat, with challenging medical treatment as no specific treatment is considered universally effective. Ibogaine has been used informally as an active in drug-assisted treatment for OUD and shown positive results. However, current evidence regarding the drug’s efficacy remains inconclusive as no consensus has been well established in literature. Aims: We aimed to perform an updated systematic review and single-arm meta-analysis of ibogaine-assisted therapy in patients undergoing treatment for opioid abuse disorders. Methods: We used PubMed, Scopus and Cochrane Central for studies that used ibogaine as a main agent in drug-assisted OUD treatment. Outcomes of interest were reduction of withdrawal symptoms, decreased substance use, improvement of social functioning and improvement of psychological symptoms. Statistical analysis was performed using OpenMetaAnalyst. Heterogeneity was assessed with I² statistics. Results: Four observational studies were included in this review, totalling 120 patients. They were predominantly of male, Caucasian individuals, with a mean age of 33.52 years and an average of 4.26 previous treatment attempts. The Subjective Opiate Withdrawal Scale (SOWS) and the Addiction Severity Index (ASI) were employed as assessment instruments. When evaluating withdrawal symptoms, meta-analysis reported overall decrease of 12.62 (95% CI: 4.75–20.48%; p = 0.003; I² = 83.05%). Significant positive changes over one year in the social functioning and mental health of patients was also relevant. However, it is important to highlight the high heterogeneity of the results, which may be explained by the relatively small sample size and the absence of control groups. Conclusion: Our meta-analysis suggests that ibogaine demonstrates promising potential for the treatment of opioid use disorder, showing beneficial effects on opioid withdrawal symptoms, psychiatric outcomes, and social reintegration of affected individuals. However, given the risk of bias inherent to the observational methodologies of the studies included in this meta-analysis, it is essential that randomized clinical trials be conducted to establish the efficacy and safety of ibogaine in this context.